The association between personal belief in a just world, voice and burnout: A cross-sectional study in a sample of national guard police officers - Val, Susana Barreto Gonçalves do (2021)
Voice is crucial both for the organizations, which benefit from new insights, and for the workers, who are able to express their concerns and ideas, having a great impact on their mental health (Cox et al., 2006). Actually, individuals who are afraid to voice are likely to show high levels of burnout (Hammond et al., 2019). In addition, continued exposure to job stressors put workers at risk of developing burnout (Penalba et al., 2008), as the case of the Republican National Guard Officers. The present study examined two parallel mediation models. The first model was a replication of a study conducted by Cheng et al. (2020), namely the association between personal belief in a just world (BJW) and voice, mediated by perceived voice efficacy (PVE) and perceived voice risk (PVR). The second model aimed to test the association between personal BJW and burnout (exhaustion and disengagement), mediated by PVE and PVR. Self-reported data was collected from National Guard Police Officers (N = 475). As expected, the results showed a positive association between personal BJW and employee voice, and a negative association between personal BJW and both dimensions of burnout. Additionally, the mediating effect of PVE was significant in both models. However, the mediating effect of PVR was only significant to the second model. These findings add knowledge to the existing literature on the fields of social psychology of justice, organizational citizenship behavior and mental health, and highlight the importance of reinforce organizational justice, by promoting BJW and voice behaviors.